Direct Observation of Molecular-Level Template Action Leading to Self-Assembly of a Porous Framework - Bajpe, Sneha R.; Kirschhock, Christine E. A.; Aerts, Alexander; Breynaert, Eric; Absillis, Gregory; Parac-Vogt, Tatjana N.; Giebeler, Lars; Martens, Johan A. (Chemistry : a European journal, 2010)
The molecular steps involved in the self‐assembly of Cu3(BTC)2 (BTC=1,3,5‐benzenetricarboxylic acid) metal–organic frameworks that enclose Keggin‐type H3PW12O40 heteropolyacid molecules were unraveled by using solution 17O, 31P, and 183W NMR spectroscopy, small‐angle X‐ray scattering, near‐IR spectroscopy, and dynamic light scattering. In aqueous solution, complexation of Cu2+ ions with Keggin‐type heteropolyacids was observed. Cu2+ ions are arranged around the Keggin structure so that linking through benzenetricarboxylate groups results in the formation of the Cu3(BTC)2 MOF structure HKUST‐1. This is a unique instance in which a templating mechanism that relies on specific molecular‐level matching and leads to explicit nanoscale building units can be observed in situ during formation of the synthetic nanoporous material. The template is the key: A strong noncovalent interaction between Cu2+ ions and Keggin‐type heteropolyacids leads to spatial organization that can be exploited for direct templating of a metal–organic framework (see figure; BTC=1,3,5‐benzenetricarboxylic acid).